Estimativas de parâmetros genéticos para a seleção precoce em clones de Eucalyptus spp. - Tambarussi, Evandro Vagner; De Lima, Bruno Marco; Da Costa Queiroz, Rafael; Peres, Fabiana Schmidt Bandeira; Da Costa Dias, Donizete; Pagliarini, Maximiliano Kawahata; Pereira, Fernanda Bortolanza [UNESP]; Rosa, João Ricardo Bachega Feijó; Peçanha Rezende, Gabriel Dehon Sampaio (My University, 2017)
This study aimed to estimate the genetic parameters and correlation between early vs. adult age in Eucalyptus spp. clones. Traits of economic interest as diameter at breast height (DBH) and height (ALT) were measured at three and five years of age. The trials were planted in randomized block design, where each experiment represented an unbalanced clonal test for number of individuals and blocks. The heritability in broad sense ( ) was low for the evaluated traits, ranging from 0.1 to 26%. However, the mean heritability ( ) was high for tests 4, 5 and 7, varying from 0.27 to 0.95 and 0.31 to 0.95 for DBH and height, respectively. The tests also showed high phenotypic correlations between traits at different ages, with values ranging from 0.79 to 0.97 for DBH, as well as high values of genetic correlations, ranging from 0.53 to 1.00. These results have fundamental importance for breeding programs for these species and to understand the correlations of early vs. adult ages.
Estimate of genetic parameters for early selection in clones of Eucalyptus spp.
Keywords: Age-age correlation.; Forest tree improvement; Genetic parameters